2013
DOI: 10.1038/aja.2013.29
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and genomics of prostate cancer

Abstract: Prostate cancer (PCa) is one of the most common malignancies in the world with over 890 000 cases and over 258 000 deaths worldwide each year. Nearly all mortalities from PCa are due to metastatic disease, typically through tumors that evolve to be hormone-refractory or castrate-resistant. Despite intensive epidemiological study, there are few known environmental risk factors, and age and family history are the major determinants. However, there is extreme heterogeneity in PCa incidence worldwide, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Despite the advances in our genomic and cellular knowledge [5], prostate cancer remains one of the major public health problems throughout the world [6, 7]. It is important that it is recently gaining recognition being highly heterogeneous and therefore encompassing a wide range of clinical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in our genomic and cellular knowledge [5], prostate cancer remains one of the major public health problems throughout the world [6, 7]. It is important that it is recently gaining recognition being highly heterogeneous and therefore encompassing a wide range of clinical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…PCa mostly affects men ≄ 60 y old, with highest incidence among African-Americans. Recent studies suggested that various host genetic, environmental, and dietary factors affect development and disease progression [1].…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, PCa is a malignant cancer, and it exhibits familial aggregation [ 9 ]. Some studies have reported that there is a strong hereditary component in the development of PCa, which accounts for 5 to 10 per cent of all cases [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%